Assessment of noise pollution and associated subjective health complaints in Jharia Coalfield, India: A structural equation model analysis - Tiwari Shashi Kant; Kumaraswamidhas Lakshmi Annamalai; Garg Naveen (Noise Mapping, 2023)
Noise pollution in the mining industry has become a serious concern in recent years and has aroused extensive health complaints for the mine workers. Despite the increasing knowledge of the association between noise exposure and health effects, only a few studies have investigated the adverse health effects due to noise pollution in the mining industry. The present study aims to determine the interrelationship of mining noise (MN), demographic characteristics (DC), noise sensitivity and noise annoyance (NA) with subjective health complaints (SHC). A PLS-SEM approach has been used to assess the direct and indirect relationship between the influencing factors on the SHC of 272 people in the mines. Field measurements were made using a sound level meter to evaluate the ambient noise levels for 1 h duration during day and night hour shifts in Dhansar and Bastacolla mining areas of the Jharia coalfield. The noise maps revealed that most of the locations have noise levels higher than 70 dB(A). The statistical model suggests that NA is the most important predictor of SHC. Besides, DC and MN induce only indirect effect on SHC. The study shall facilitate in developing a decision support tool for the assessment of noise levels, induced annoyance, SHC, and suitable policy interventions for controlling noise exposure among mine workers in the coalfield.